Interplay between long‐term vulnerability and new risk: Young adolescent and maternal mental health immediately before and during the COVID‐19 pandemic. Issue 1 (18th May 2021) - Wright, Nicola; Hill, Jonathan; Sharp, Helen; Pickles, Andrew
Abstract: Background: We examine whether there has been an increase in young adolescent and maternal mental health problems from pre‐ to post‐onset of the COVID‐19 pandemic. Methods: Children aged 11–12 years and their mothers participating in a UK population‐based birth cohort (Wirral Child Health and Development Study) provided mental health data between December 2019 and March 2020, and again 3 months after lockdown, 89% ( N = 202) of 226 assessed pre‐COVID‐19. Emotional and behavioural problems were assessed by self‐ and maternal reports, and long‐term vulnerability by maternal report of prior child adjustment, and maternal prenatal depression. Results: The young adolescents reported a 44% (95% confidence interval [CI: 23%–65%]) increase in symptoms of depression and 26% (95% CI [12%–40%]) for post‐traumatic stress disorder, with corresponding maternal reports of child symptoms of 71% (95% CI [44%–99%]) and 43% (95% CI 29%–86%). Disruptive behaviour problem symptoms increased by 76% (95% CI [43%–109%]) particularly in children without previous externalising symptoms. Both female gender and having had high internalising symptoms earlier in childhood were associated with elevated rates of depression pre‐pandemic, and with greater absolute increases during COVID‐19. Mothers' own depression symptoms increased by 42% (95% CI [20%–65%]), and this change was greater among mothers who had prenatal depression. No change in anxiety was observed among children or mothers. None of these increases were moderated by COVID‐19‐related experiences such as frontline worker status of a parent. Prior to the pandemic, rates of maternal and child depression were greater in families experiencing higher deprivation, but changed only in less deprived families, raising their rates to those of the high deprivation group. Conclusions: COVID‐19 has led to a marked increase in mental health problems in young adolescents and their mothers with concomitant requirements for mental health services to have the resources to adapt to meet the level and nature of the needs. Abstract :